2013
DOI: 10.1002/bjs.9000
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of percutaneous versus transcutaneous posterior tibial nerve stimulation in faecal incontinence

Abstract: NCT00530933 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 31 publications
3
89
1
1
Order By: Relevance
“…Furthermore, improvements in patient quality of life have been observed. 22,24,25,26,27 Consistently, PTNS also improved the FI score and quality-of-life values in our study. In addition, 15 (68%) patients experienced more than 50% reduction in the number of FI episodes.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, improvements in patient quality of life have been observed. 22,24,25,26,27 Consistently, PTNS also improved the FI score and quality-of-life values in our study. In addition, 15 (68%) patients experienced more than 50% reduction in the number of FI episodes.…”
Section: Discussionsupporting
confidence: 87%
“…However, in many studies, the anorectal physiological test results, which were performed after the treatment, did not change despite clinical improvements. 5,22 Despite the significant clinical improvement in the PTNS group, in their randomized trial, George et al 26 reported that there was no significant difference between the PTNS and placebo group in terms of anorectal physiological tests. Moreover, some data have indicated that post-treatment results are not related to the pretreatment anal manometer tests and anal ultrasound results.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In selected patients with multiple sclerosis (i.e, with less severe, stable disease and low symptom load) there may be a role for this technique. Less invasive procedures like tibial nerve stimulator have been shown to be effective in managing bowel function in patients with idiopathic incontinence and are being assessed for their use in improving bowel function in multiple sclerosis patients [32,33].…”
Section: Interventionsmentioning
confidence: 99%